PENINGKATAN KECERDASAN KINESTETIK MELALUI KEGIATAN BERMAIN SIRKUIT DENGAN BOLA (Penelitian Tindakan di Kelompok A TK Al Muhajirin Malang Jawa Timur, Tahun 2015) - Denok Dwi Anggraini (PG-PAUD Trunojoyo, 2015)
Increase Kinesthetic Intelligence Through Play Activities Circuit With Ball. The purpose of this research was to determine the process of implementation of the circuit with a ball playing in increasing child kinesthetic intelligence in group A in Al Muhajirin Kindegarten Malang and to know the extent to which the results of the increase in child kinesthetic intelligence through a circuit with a ball playing in group A Al Muhajirin Kindegarten Malang.The method used in this research is an action research which refers to the model of a Classroom Action Research Kemmis and Mc. Taggart consist of four phase: planning, action, observation and reflection. This research consist of two cycles, each cycle consist of 8 times in actions. Analysis of the data used quantitative and qualitative approaches. The results showed an increase kinesthetic intelligence through circuits with a ball playing activities, it can be proven scoring average pre-action children's kinesthetic intelligence by 32.81%. And then increased in the first cycle by 37.44% to become 70.25%. Furthermore, from the first cycle to the second cycle kinesthetic intelligence of children increased by 17.91% from 70.25% to 88.16%. So the total increase kinesthetic intelligence of children ranging from pre-action, the first cycle to the second cycle is 32.81% 70.25% to 88.16%.